Effect of non-thermal atmospheric pressure plasma and ErCr:YSGG LASER activation of three fluoride varnishes on surface re-mineralization of enamel: A SEM-EDX analysis - Shreya Arun Bapat; N D Shashikiran; Sachin Gugawad; Namrata Gaonkar; Swapnil Taur; Savita Hadakar; Pradnya Chaudhari (Wolters Kluwer Medknow Publications, 2022)
Background: Dental remineralization is the process of transporting minerals from the surrounding environment (i.e., saliva and biofilm) into partially demineralized tooth structures. Remineralization can be induced by professional therapies such as fluoride-based treatments that have the highest level of supporting evidence. High-intensity LASER and nonthermal atmospheric pressure plasma therapy have been known to increase the resistance of enamel to demineralization by surface modification. Aim: The aim of the study was to evaluate and compare the surface remineralization of enamel using ErCr:YSGG LASER and nonthermal atmospheric pressure plasma (NTP) activation with three different fluoride varnishes. Methodology: Sixty-eight extracted premolars were used which were sectioned mesiodistally to obtain 135 specimens and artificial caries were induced on the experimental surface. They were then randomly divided into three groups (n = 45): MI Varnish (GC Japan), Vanish Varnish (3M ESPE), and Embrace Varnish (Pulpdent). After varnish application, these groups were further divided into three subgroups based on the activation therapy used. Fifteen samples from each group were treated with ErCr:YSGG LASER, 15 samples with NTP, and 15 samples were the control that did not undergo activation. After 9 days of pH cycling, the mean ion concentration of the surface calcium and phosphate ions was recorded using FEG-SEM and EDX analysis. The data were statistically analyzed. Results: One-way ANOVA and post hoc Tukey test accepting P < 0.05 were performed for comparisons between all analyses groups. Vanish Varnish showed a higher Ca/P ratio in LASER, NTP, and control subgroups, followed by MI Varnish and Embrace Varnish. ErCr:YSGG LASER therapy showed an improved Ca/P ratio in all varnishes than NTP therapy and control. Conclusion: ErCr:YSGG LASER therapy showed positive effects toward improving the Ca/P, followed by NTP therapy as compared to control in all three varnishes indicating their role in enhancing the effects of remineralization. Vanish Varnish showed a higher Ca/P ratio indicating better remineralization post activation.